2010
DOI: 10.1007/s11165-009-9152-y
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating the Inquiry Question: A Comparison of Whole Class and Small Group Strategies in Grade Five Science Classrooms

Abstract: The purpose of this study is to examine the effect of two strategies for negotiating the question for exploration during science inquiry on student achievement and teachers' perceptions. The study is set in the context of the Science Writing Heuristic. The first strategy (small group) consisted of each group of four students negotiating a question for inquiry with the teacher while the second strategy (whole class) consisted of the entire class negotiating a single question for inquiry with the teacher. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
2
4
0
1
Order By: Relevance
“…It was determined that pre-service teachers who experienced ATBÖ process changed their perspectives on learning and made better understanding of constructivist learning. These results support the view that the learning environment dominated by ATBÖ process creates opportunities for the constructivist learning environment (Cavagnetto, et al, 2010;Hand & Keys, 1999).…”
Section: Findings Discussion and Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…It was determined that pre-service teachers who experienced ATBÖ process changed their perspectives on learning and made better understanding of constructivist learning. These results support the view that the learning environment dominated by ATBÖ process creates opportunities for the constructivist learning environment (Cavagnetto, et al, 2010;Hand & Keys, 1999).…”
Section: Findings Discussion and Resultssupporting
confidence: 78%
“…Argümantasyon Tabanlı Bilim Öğrenme (ATBÖ) yaklaşımının öğrencilerin bu ihtiyacına cevap verebilecek niteliğe sahip olduğu söylenebilir. Çünkü temelinde bilimsel sorgulamanın olduğu ATBÖ yaklaşımı öğrencilerin bilimsel sorgulama içinde, bilimsel bilgiyi yapılandırmalarına yardım etmek adına tasarlanmış bir öğrenme yaklaşımıdır (Cavagnetto, Hand, & Norten-Meier, 2010;Hand & Keys, 1999). Bu süreçte oluşan bilimsel argümantasyon; iddia ve verinin, gerekçelendirmeler ile birlikte, hem deneysel hem de teorik anlamda bağlantılar kurma sürecidir (Erduran & Jimenez-Aleixandre, 2007).…”
Section: Introductionunclassified
“…For example, a three-year, mixed method study by Hand, Norton-Meier, Gunel, and Akkus (2015) that included 32 elementary teachers from six school districts and over 700 students each year demonstrated that, "critical embedded language opportunities contribute to an increase in student Iowa Tests of Basic Skills (ITBS) scores in science and language based on level of implementation particularly for elementary students who receive free and reduced lunch (an indicator of living at poverty level)" (Hand et al, 2015, abstract). The use of the Science Writing Heuristic (SWH) in this study and in previous studies with grade five students (Cavagnetto, Hand, & Norton-Meier, 2011) and with younger students in kindergarten through third grade (Linebarger & Norton-Meier, 2016) have also indicated an increase in the understanding of challenging science content.…”
Section: "Writing To Learn" To Meet Demand For Science Literacysupporting
confidence: 71%
“…We present the negotiation model to demonstrate how to engage students in using the scientific argument structure to learn science' s big ideas through argumentative practices. Empirical studies have shown that engaging students in the negotiation model can help them develop deeper conceptual understanding, advance critical thinking skills, and promote literacy in science (Cavagnetto et al, 2011;Chen, 2011;Nam et al, 2011). It is time for all of us to move away from activity-driven inquiry to argument-based inquiry in which students can construct and critique scientific knowledge through authentic and core practices of science.…”
Section: The Relationship Between a Claim And Evidencementioning
confidence: 99%